Management of Facilities and Infrastructure in Improving the Learning Process - Singgih Hari Pangestu; Hasan Hariri (Jurnal Humaniora dan Ilmu Pendidikan, 2022)
The background of this research is that every school has facilities and infrastructure, whether adequate or inadequate. Facilities and infrastructure need to be utilized and managed for the benefit of the learning process.  This management is intended so that the use of facilities and infrastructure can running effectively and efficiently. Purpose: The aims of this study were to find out facilities and infrastructure management based on literature review from previous research from several countries around the world. Methodology: The method used in this research is human instrument, descriptive qualitative, case study, with retrieval data in the form of interviews, observations, and documentation. Results: The result of this review that already fulfilled by means of: requirements planning, procurement, use, maintenance, inventory, write-off and liability. For teacher can use a means and infrastructure for teaching, for school to have a facilities and infrastructure and can help a students and teachers for study, to other authors that further research using facilities and infrastructure of study applied to other materials. Facility management and infrastructure at SMP N 2 Sragi already according to management techniques, which include planning, procurement, Distribution, use and maintenance. Limitations: One of the factors that became obstacles and obstacles in this study was the time and place of research. Contribution: This research can contribute in Educational Institutions, school management, educational foundations, and also implemented by teachers in educational institutions.